PENGARUH DISIPLIN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT HERO SUPERMARKET TBK CABANG GIANT EXTRA METROPOLITAN CITY PEKABARU - Manik, Sudarmin; Syafrina, Nova (Sekolah Tinggi Ilmu Ekonomi Riau, 2017)
The purpose of this study is to determine the effect of work discipline on employee performance at PT. Hero Supermarket Tbk Branch Giant Extra Metropolitan City Pekanbaru .. Population in this research is employees of PT. Hero Supermarket Tbk Branch of Giant Extra Metropolitan City Pekanbaru which amounted to 102 people. Sampling is done by using sampling method. Data analysis was performed using reliability test, normality, F test, multiple linear regression, R2 test and t test. The test is conducted in order to determine the effect of work discipline on employee performance at PT. Hero Supermarket Tbk Branch of Giant Extra Metropolitan City Pekanbaru. Based on the results of research that the service quality simultaneously factors that affect the compensation with the correlation value R = 0.673 which indicates a close relationship between work discipline and organizational culture with employee performance. While adjusted R square in can 0,427, which means work discipline and organizational culture contribute 42,7% contribution to employee performance, and have positive and significant influence to employee performance with level of sig. 0,000. The conclusion from the research that hypothesis simultaneously and partially between work discipline and organizational culture have a significant effect on employee performance proven and acceptable truth